2003
DOI: 10.1145/859670.859695
|View full text |Cite
|
Sign up to set email alerts
|

Extracting library-based Java applications

Abstract: Reducing the size of Java applications by creating an application extractor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Rayside et al [RK02], Jax [TSL03] and the ExoVM System [Tit06] propose application extraction tools using these techniques for Java applications. Sallenave et al [SD10] apply RTA to produce smaller .NET assemblies for embedded systems.…”
Section: Static Analysis-based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rayside et al [RK02], Jax [TSL03] and the ExoVM System [Tit06] propose application extraction tools using these techniques for Java applications. Sallenave et al [SD10] apply RTA to produce smaller .NET assemblies for embedded systems.…”
Section: Static Analysis-based Techniquesmentioning
confidence: 99%
“…The majority of the solutions to this problem described in the literature [RK02,TSL03,Tit06,SD10,BO14,Age96] propose to automatically detect and extract useful code, so called tailoring, with static call graph construction [GDDC97] (Section 6). These static approaches present several limitations:…”
Section: Introductionmentioning
confidence: 99%
“…Butts [3] has shown that approximately 3% to 16% dead or unreachable code exists in programs. Tip and Sweeney [22,21,23] reduce the size of Java applications by using an application extractor. Like our approach, their aim is to ship only needed class files to a mobile device, cut out never invoked methods, and perform some name compression of the constant pool.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work [8], we have overridden this classical usage of romization and shown the benefits of going further in the system deployment during romization: the romizer can perform very aggressive customizations on the system if the latter is deployed far enough. In particular, call graph analyses [9] on the threads allow unused parts of the APIs to be removed using library extraction techniques [10,11], and the remainder to be specialized for runtime usage. This results in APIs that are custom-tailored on a per-case basis for the system, and have low memory footprints.…”
Section: Previous Work On Romizationmentioning
confidence: 99%